The Influence Of Leadership, Commitment, And Motivation On Employee Performance, Mediated By Job Satisfaction, In Belitung Land Offices - Antonius Bagus Budhi Pradhana; Ikhwan HS; Ana Sriekaningsih (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the effect of leadership style, organizational commitment, and motivation on employee performance with job satisfaction as a mediating variable in the Belitung Regency Land Office and the East Belitung Regency Land Office. The method used in this research is quantitative with primary data collection through questionnaires. The sample used in this study was the entire population of employees of the Belitung Regency Land Office and the East Belitung Regency Land Office totaling 110 people. The data analysis technique used SEM PLS with the Smart PLS 4 application. The results showed the following: Leadership style has a significant and positive effect on job satisfaction; organizational commitment has a significant and positive effect on job satisfaction; work motivation has a significant and positive effect on job satisfaction; leadership style has no significant effect on employee performance; organizational commitment has no significant effect on employee performance; work motivation has a significant and positive effect on employee performance; job satisfaction has a significant and positive effect on employee performance; leadership style has a significant effect on employee performance through job satisfaction as a mediating variable; organizational commitment also has a significant effect on employee performance through job satisfaction; and work motivation is proven to have a significant effect on employee performance through job satisfaction.